Africa RISING Tanzania- Intensifying Maize-Based Cropping Systems Through Pigeonpea Integrations - World Agroforestry Centre; Sokoine University of Agriculture (International Food Policy Research Institute, 2016)
Yield advantages in intercropping are determined by the net effects of positive (facilitative and complementarity) interactions and mitigating negative (competitive) interactions. Pigeonpea plants have both physiological and morphological attributes that may reduce interspecific competition in mixed culture. The initial slow growth of pigeonpea relative to cereals minimizes competition in intercropping systems, making pigeonpea compatible with most cereal-based systems. In semi-arid areas, however, growing seasons are increasingly becoming shorter because of low and sporadic rainfall. Consequently, yield of intercropped pigeonpea may be adversely affected by competition, if farmers do not use appropriate agronomic practices. Pigeonpea is a fairly new legume crop in Kongwa and Kiteto districts, requiring both adaptability studies and agronomy studies particularly for sustainable intensification purposes. Thus, this study is being carried out to assess the component interactions and their impacts on farm productivity in order to provide guidelines for optimizing yields of maize and pigeonpea in semi-arid climates of Central Tanzania. Project title: Africa RISING. Project abstract: The aim of the Africa RISING project in Kongwa and Kiteto Districts, Tanzania is to provide a scientific basis for sustainably intensifying agricultural production in semi-arid areas of central Tanzania. The project activities are falls under 4 thematic areas that address three critical elements of sustainable intensification (SI), i.e. genetic, ecological and socio-economic intensification technologies. The scope of activities being implemented include: packaging of new legume and cereal varieties with over 120% yield advantage, packaging and validation of integrated productivity enhancing technologies for cereals, legumes, legume trees and soil health technologies, food safety primarily to reduce aflatoxin contamination and integration of livestock into the cropping systems. The innovation platform is used to set R4D priority in the action sites. In the 2013-2014 season, we reached out to about 1217 farmers Kongwa and Kiteto districts. In 2014 we plan to reach out to about 1500 new farmers. The project team is comprised of national partners (e.g. ARI-Hombolo, District Agricultural Officers, SUA and UDOM) and CG Partners (CIMMYT and ICRAF) under the leadership of ICRISAT. Project website: http://africa-rising.net